Hysteroscopic septal resection using unipolar resectoscope versus bipolar resectoscope: Prospective, randomized study. Issue 6 (10th December 2014) - Roy, Kallol Kumar; Kansal, Yamini; Subbaiah, Murali; Kumar, Sunesh; Sharma, Jai Bhagwan; Singh, Neeta
Abstract Aim To compare the operation and reproductive outcome of hysteroscopic septal resection using unipolar resectoscope verses bipolar resectoscope. Methods In this prospective randomized study, 70 women underwent hysteroscopic septal resection using either unipolar resectoscope or bipolar resectoscope. Intraoperative parameters (operation time, fluid deficit and complications) and pre‐ and postoperative serum sodium levels were compared between the two groups. A second‐look hysteroscopy was performed after 6 weeks. All pregnancies occurring during the follow‐up period were recorded. Results There was no statistically significant difference between the two groups in terms of operation parameters and second‐look hysteroscopy findings. Six patients in the unipolar group were found to have hyponatremia in the postoperative period compared to none in the bipolar group (P = 0.025). Regarding reproductive outcome, the difference between the two groups was not significant. Conclusion The use of bipolar resectoscope is associated with lesser risk of hyponatremia compared to unipolar resectoscope. Bipolar resectoscopy is a safe alternative to unipolar resectoscopy with similar reproductive outcome.